2011
DOI: 10.1038/sc.2011.16
|View full text |Cite
|
Sign up to set email alerts
|

Return to work after spinal cord injury: factors related to time to first job

Abstract: Study design: Cross-sectional survey. Objectives: To investigate factors related to length of time between spinal cord injury (SCI) onset and start of first post-injury employment. Setting: Persons living with SCI in the community who are members of a disability support organization. Methods: Participants were randomly selected from the membership list of a non-governmental voluntary organization. They met the following four criteria: traumatic SCI, minimum of 15 years of age at the time of survey, a minimum o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
42
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(45 citation statements)
references
References 13 publications
(19 reference statements)
2
42
0
1
Order By: Relevance
“…5,48 However, consideration also needs to be given to the period of time between an individual's discharge from the in-patient spinal injury rehabilitation unit and employment. 6 For some people, the psychological impact of a SCI is chronic, hence there may be a considerable delay before employment goals are achieved. 3,6,8,49 There is a need then, for future research to examine referral pathways and, in particular, to explore barriers to the use of vocational services for people with SCI.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…5,48 However, consideration also needs to be given to the period of time between an individual's discharge from the in-patient spinal injury rehabilitation unit and employment. 6 For some people, the psychological impact of a SCI is chronic, hence there may be a considerable delay before employment goals are achieved. 3,6,8,49 There is a need then, for future research to examine referral pathways and, in particular, to explore barriers to the use of vocational services for people with SCI.…”
Section: Discussionmentioning
confidence: 99%
“…6 For some people, the psychological impact of a SCI is chronic, hence there may be a considerable delay before employment goals are achieved. 3,6,8,49 There is a need then, for future research to examine referral pathways and, in particular, to explore barriers to the use of vocational services for people with SCI.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…1 Returning to work for the pre-injury employer is one of the most significant factors relating to both employment following SCI and time taken to return to work. 19,20 Studies have found that a 'fast track' exists whereby individuals with SCI who return to work for their pre-injury company, whether in the same role or a new role, return to work significantly faster than those who find employment with a new company. This key piece of information should have a crucial role in future attempts to improve employment outcomes post-SCI.…”
Section: Introductionmentioning
confidence: 99%